Преобразуйте в многочлен: а) 9x^2-(y-3x)^2 б) (5a+7)^2-70a в) c(1+2c)^2 г) -6(2x-y)^2 д) (p+7)*p-(1-p)

ponomareva1947 ponomareva1947    2   22.07.2019 09:20    1

Ответы
artemchurkin artemchurkin  03.10.2020 10:28
А) 9x^{2} -(y-3x) ^{2} = 9x^{2} -( y^{2} -6xy+9 x^{2} )=9x^{2} -y^{2} +6xy-9 x^{2} ==6xy -y^{2} ;
б) (5a+7)^{2} -70a=25 a^{2} +70a+49-70a=25 a^{2} +49;
в) c(1+2c)^{2} =c(1+4c+4 c^{2} )=c+4 c^{2} +4 c^{3} ;
г) -6(2x-y)^{2} =-6(4 x^{2} -4xy+ y^{2} )=-24 x^{2} +24xy-6 y^{2} ;
д) (p+7)p-(1-p)= p^{2} +7p-1+p= p^{2} +8p-1.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра